Niveles séricos de la hormona antimülleriana en donadoras brahman y su efecto en la respuesta superovulatoria y la produccción de embriones - Intriago Loor, Wilian Alejandro (2019)
The objective of this research was to assess the effect of AMH levels on the superovulatory response and embryo production in vivo. Ten Brahman donors subjected to a traditional superovulation protocol with 1 or 0.5 g of progesterone (cows and heifers respectively), 2.5 mg of estradiol benzoate and decreasing dose of FSH (350 IU cows and 250 IU heifers) were used. All the data were analyzed with statistical software Statistix 8.0 where Pearson correlations and T - Student tests (0.05%) were performed. AMH levels were divided into ranges from 100 to 255 and 256 to 700 picograms/milliliter (ρg/mL). There was no correlation between AMH levels and total transferable embryos (P=0.70). A correlation was found between the levels of AMH and the total number of follicles present in the follicular count on Day 0 (P=0.06). There were significant differences (P=0.0031) in the number of follicles between cows with high AMH levels (256 to 700 ρg/mL) with respect to those of low level (100 to 255 ρg/mL). No significant differences were found between the ranges of AMH and the total of corpora lutea (P=0.60). Likewise, when comparing the total embryos in cows and heifers, no significant differences were found (P=0.60). In conclusion, the levels of AMH correlate positively with the follicular population prior to the start of the superovulation protocols. The results showed that at a higher level of AMH there is a greater follicular population in Brahman donors.